(untitled) (Journal of Geography and Environmental Management, 2022)
Since precipitation affects many sectors, in particular agriculture, economics, construction, energy, oil and gas industry, identifying precipitation trends, seasonal anomalies and obtaining reliable precipitation data is essential for long-term weather compilation. To this end, this article revealed the trend of seasonal changes in precipitation during the warm season at the meteorological stations Astana, Atbasar, Kokshetau, Kostanay, Petropavlovsk and Pavlodar in Northern Kazakhstan in the period from 1950 to 2020 and calculated the main statistical characteristics. The study found that in the northern region of Kazakhstan in the period from 1950 to 2020, the trend towards an increase in precipitation during the warm period increased at a rate of 0.2-11.2 mm every 10 years. In the northern region of Kazakhstan, the maximum amount of precipitation during the warm season varied within 60-208 mm at the stations under consideration and was recorded in July and August. The minimum amount of precipitation varies between 0.2-21 mm, most often observed in April and September. Among the stations where the trend towards an increase in the amount of precipitation in the 1st and 2nd half of summer was considered, at Pavlodar station it was high (α=6 mm/10 years). When determining the statistical structure in the north of Kazakhstan, the values ​​of the kurtosis coefficient were observed above the critical values ​​only in spring at Atbasar station, in the 1st half of summer at Atbasar and Pavlodar stations, in the 2nd half of summer at Atbasar, Petropavlovsk and Pavlodar stations.